CONSTRUCTIVE DISMISSAL: A TRICKY HORSE TO RIDE Jordaan v CCMA 2010 31 ILJ 2331 (LAC) - N Whitear-Nel; Matthew Rudling (Obiter, 2021)
The concept of constructive dismissal is flexible because the circumstances that may give rise to it are “so infinitely various” (Minister of Home Affairs v Hambidge 1999 20 ILJ 2632 (LC) par 12). As such, there are no clear rules defining precisely when a constructive dismissal has taken place. The facts of each case must be established, interpreted and measured against general principles to determine whether the requirements for constructive dismissal have been met. The Labour Appeal Court (LAC), in the case of Jordaan v CCMA (2010 31 ILJ 2331 (LAC) 2335), made the point that the law has attained more certainty since Hambidge’s case. This is partially true. However, this case note shows that it remains difficult to set down hard and fast rules to determine the existence of a constructive dismissal. The Supreme Court of Appeal (SCA) has held that very strict proof of constructive dismissal is required, and it has not readily found that circumstances complained of by employees constitute such a dismissal. In the case of Old Mutual Group Schemes v Dreyer (1999 20 ILJ 2030 (LAC)) Conradie JA cautioned that constructive dismissal is not for the asking. He held that generally it will be difficult for an employee who resigns to show that he has actually been constructively dismissed, because the onus of proof on the employee in this regard is a heavy one. Jordaan’s case highlights just how hard it is to establish a viable claim of constructive dismissal. It shows that even where an employee experiences a loss of job security as a result of attempts by the employer to protect his business, and this leads to the employee’s resignation, it will not rise to the standard of constructive dismissal. The LAC saw Jordaan’s case as an attempt to “stretch the law relating to constructive dismissal” and held that this was not only inappropriate but that such an attempt “should not be contemplated” by future courts.